The Rise of the Knowledge School and Its Relation to the Resurrection of Bildung - Wedin, Tomas (Nordic Journal of Educational History, 2015)
In this article the historical background to the reactivation of the concept of Bildung in the Swedish school debate during 1980s is presented. The article argues that the resurrection of this concept is intimately related to the foundation of the discourse of the Knowledge School (Kunskapsskolan), and shows how these two terms were central in school political program developed by the Knowledge Movement (Kunskapsrörelsen) in the early 1980s. The article shows how the concept of Bildung since it was resurrected not only has been highly contested, but that it was actually reactivated within the same movement that helped pave the way for the manifest economic-instrumentalist school discourse that dominates the current curriculum.